(untitled) (Research, Society and Development, 2019)
This article aims to identify the elements that characterize Science Teaching as object of social representations from the theoretical methodological approach of Theory of Social Representations. Based on the reflections of Farr, which refers to the theory as a sociological form of Social Psychology, originated from the studies of Moscovici, based on the text, Social Representations: theory and its history, of the author, being the text part of the organization of the work: Texts in Social Representations of Jovchelovitch and Guareschi. Having the theoretical contribution of Sá on the construction of the object of research, the interdisciplinary practice of teachers of the Initial Years, anchored in the studies of the theorists: Japiassu, Fazenda and Pombo that discuss the term interdisciplinarity. The studies for this work are based on conceptualizations about the term interdisciplinarity, and the identification of the social representations of the research subjects, a group of teachers from the Initial Years of Elementary School, for such a review of the literature was carried out with contributions in the mentioned authors. The applied methodology is based on literature review and qualitative research. The Bardin Content Analysis was used to anchor the analysis and reflection on the data collected. From the analysis it was possible to identify the social representations of the subjects of the research on the conceptualization of the term interdisciplinarity, as one of the elements that characterize the Teaching of Sciences, which are based on the knowledge acquired by the formation and according to the social group to which they belong. They stand out as elements that characterize the Science Teaching in the collected data, the interdisciplinary practice as object of research, taking into account the intention of the subjects of the research in realizing an interdisciplinary practice when performing the teaching work.